New forms of electronic media and their impact on public policy making: three cases from Egypt - Farag, Doaa Alaa El Din (AUC Knowledge Fountain, 2011)
There is an increasing rise in the popularity of electronic media, especially Facebook and YouTube in the Arab world, and in Egypt in particular. This reflects an important indication of the growing influence of Facebook and YouTube on the Egyptian society and on Egypt's political stream. The purpose of this study is to answer the main research question, which is to what extent does electronic media affect public policy making in Egypt, with regards to three cases studies. They include the Egyptian/Algerian football conflict, as a result of a soccer match qualifying the winning team to the World Cup 2010, the face-veil controversy, banning women wearing the face-veil to enter public university examinations, and the Fair Access Policy limiting Internet download for DSL and ADSL subscribers. The objective is to determine whether electronic media has the power to mobilize public opinion towards a certain cause, which may then affect government action. This would allow us to realize first the power and influence of mainstream media, followed by electronic media, and the factors that affect Egypt's policy making decisions. The methodology adopted in this study include a review of literature, a qualitative study, that includes interviews with media and political science experts, and a quantitative study surveying 238 students from The American University in Cairo and Cairo University. Respondents for the in-depth interviews were selected based on their professional expertise, and the respondents for the survey were based on a non-probability convenient sample from The American University in Cairo and Cairo University students, which represent a sample of Egyptian youth coming from different socio-economic backgrounds. The study findings indicate that electronic media affects public policy making decisions to a certain extent and on a case by case basis. Although Egypt is a non-democratic country, whose policies do not get affected easily by public opinion, the mobilization of educated youth through online social networks, such as Facebook and YouTube, are growing in influence and are having an impact on Egypt's political stream. The findings of the study reveal that the government is paying attention to online social networks, which is indicated from the arrests of online political activists and bloggers, and its response to the public outcry on the Egyptian/Algerian football conflict. There is also evidence that the mobilization of Internet users through Facebook groups is linked to the government's decision to reverse the Fair Access Policy two weeks after it was announced. As for the face-veil controversy, online discussions are affecting public opinion and public debate, however, there is no direct link on the court decision to ban or allow women wearing the face-veil to enter public university examinations.